Down-Regulation of USP8 Suppresses HER-3 Positive Gastric Cancer Cells Proliferation - Sun, Jiangang (Onco Targets Ther, 2020)
BACKGROUND: Ubiquitin specific peptidase 8 (USP8) has been reported to induce the degradation of several receptor tyrosine kinases such as epidermal growth factor receptor (EGFR), among which human epidermal growth factor receptor-3 (HER-3) is one of them. However, the role and functional mechanisms of USP8 and HER-3 in gastric cancer (GC) remain unknown. OBJECTIVE: To explore the function and mechanism of USP8 and HER-3 in the progression of GC. MATERIALS AND METHODS: Eighty-eight patients with histologically confirmed GC were recruited for this study. Tumor samples and GC cell lines were used to detect USP8 and HER-3 levels. MGC803 (HER-3 negative GC cell) was selected as the control group and NCI-N87, MKN-45 and AGS (HER-3 positive GC cells) as the experimental group. USP8i and si-RNA were then used to down-regulate USP8 in each group. Apoptosis and cell-cycle experiments were performed to detect the effects of USP8 on GC cells. Cytotoxicity Assay Kit (MTT) and colony formation assays were used to analyze cell proliferation. Cell migration and invasion ability were examined by wound healing. The expression of related mRNA and protein was detected by Western blot and quantitative real-time PCR (qRT-PCR). In vivo experiments were used to examine the effect of USP8 and HER-3. RESULTS: Patients with high expression of USP8 or HER-3 tumors alone died earlier than those with low expression and the patients with both USP8 and HER-3 high expression had a shorter overall survival than those with the opposite pattern (both USP8 and HER-3 low expression). Down-regulation of USP8 inhibited cell proliferation and cell metastasis and also reduced the HER-3 expression. We also observed that down-regulation of USP8 inhibited the proliferation of GC cells which highly expressed HER-3. Moreover, down-regulation of USP8 could promote the apoptosis of HER3-positive GC cells and inhibit the proliferation of them by affecting the cell-cycle. In vivo studies demonstrated that down-regulation of USP8 inhibited HER-3 positive tumors growth. CONCLUSION: Down-regulation of USP8 inhibits HER-3 positive GC cells proliferation in vivo and in vitro, which indicate that USP8 represents a feasible choice as a therapeutic target for HER-3 positive GC cells.